ANALYSIS OF MUSCULOSKELETAL DISORDERS COMPLAINTS OF ASSEMBLY AND DECORATION AREA WORKERS AT PT. X - Chusumadinata, Alhabsy; Wahyudiono, Yustinus Denny Ardyanto; Mulia, Shinta Arta; Wicaksono, Bagus (HEARTY, 2024)
One of the tasks of humans in the industrial world is moving and transporting materials at great risk of triggering Musculoskeletal Disorders (MSDs). One production area with the potential for occupational disease hazards is the Assembly and Decoration area, which is a place for mixing colors. This area has a fairly high potential for occupational diseases in the form of MSDs because everyday workers always use manual product handling or what is known as lifting for 8 hours, hence workers often experience complaints of MSDs on the back, waist, shoulders, and arms. This research is a descriptive quantitative research type with analytical observational methods. This research is cross-sectional. The population in this study was 30 workers in the assembly and decoration area of ​​PT. X. Measurement of MSDs among workers in the Assembly and Decoration areas using the Nordic Body Map (NBM) questionnaire and the RULA method. The results of measurements using the Nordic Body Map (NBM) questionnaire show that workers in the Assembly and Decoration sections have the potential to experience MSDs problems. Apart from that, based on the results of RULA measurements on Assembly and Decoration workers, a total score of 5 was obtained. So it can be concluded that this work is in the medium category and action is needed soon.